1992
DOI: 10.1007/bf00351663
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of a plastid-encoded groEL homologous heat-shock gene in a thermophilic unicellular red alga

Abstract: A gene homologous to the E. coli groEL locus was identified on the plastid genome of the unicellular red alga Cyanidium caldarium strain 14-1-1 (synonym: Galdieria sulphuraria). The complete nucleotide sequence was determined and compared to bacterial- and nuclear-encoded counterparts of higher plants. At the amino-acid level the C. caldarium gene shows 70% homology to the corresponding gene of the cyanobacterium Synechococcus and 52% homology to nuclear-encoded counterparts of higher plants, respectively. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Second, red algal plastids encode more proteins than do green plastids, and some of these extra genes were shown to be regulated at the transcriptional level. For example, the plastid groEL gene encoding chaperonin 60 is transcriptionally activated during acclimation to high temperature in Porphyra umbilicalis and Cyanidium caldarium (Reith and Munholland, 1991;Maid et al, 1992). As described above, we found that transcripts of plastid genes of C. merolae including ycf24, ycf16, and ftsH that are not present in the plastid genome of higher plants rapidly accumulated with illumination (Figure 1, 2, Table 1), and this accumulation could be were considered using PAUP 4.0b10 (Swofford, 2002) and calculated using TREE-PUZZLE 4.0 based on the JTT model (Jones et al, 1992) with 100 puzzling steps (Strimmer and von Haeseler, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Second, red algal plastids encode more proteins than do green plastids, and some of these extra genes were shown to be regulated at the transcriptional level. For example, the plastid groEL gene encoding chaperonin 60 is transcriptionally activated during acclimation to high temperature in Porphyra umbilicalis and Cyanidium caldarium (Reith and Munholland, 1991;Maid et al, 1992). As described above, we found that transcripts of plastid genes of C. merolae including ycf24, ycf16, and ftsH that are not present in the plastid genome of higher plants rapidly accumulated with illumination (Figure 1, 2, Table 1), and this accumulation could be were considered using PAUP 4.0b10 (Swofford, 2002) and calculated using TREE-PUZZLE 4.0 based on the JTT model (Jones et al, 1992) with 100 puzzling steps (Strimmer and von Haeseler, 1996).…”
Section: Discussionmentioning
confidence: 99%